Propaganda Jepang melalui Majalah Djawa Baroe pada Masa Kependudukannya di Indonesia - Raisa Hashina Rosalini; Desi Dwi Prianti (Jurnal Komunikasi, 2022)
War and propaganda become two inseparable aspects. When its occupation in Indonesia, Japan used various tool to influence and attract Indonesian’s attention. Mass media became the most accessible tool used by Japan to give the doctrines and propaganda, especially Djawa Baroe magazines. This paper aims to analyze how the Japanese use the media, especially Djawa Baroe magazine, produced in 1943 in Indonesia as a propaganda tool in doctrine and mobilize its dominated society through the discourse analysis approach. The research was conducted through three stages of analysis, in which the results of the analysis were analyzed profoundly through the view of critical discourse analysis. The result shows six-issues categories can be discussed from 250 articles in Djawa Baroe magazine. Japanese military powers; area security by Japan; education, training, and knowledge were given to society; Japan and “the older brother”; enemies; and, community testimony and response. As a result, propaganda, doctrine and the application of Japanese cultural influences can be seen in the style of language, the use of sentences and images displayed in the article. Doctrine given by the Japanese government includes various aspects such as threat and fear from the enemies and kindness and attention.